2005
DOI: 10.1097/01.olq.0000161177.21639.96
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sexually Transmitted Infections Among Female Sex Workers in the Eastern Highlands Province of Papua New Guinea: Correlates and Recommendations

Abstract: STIs are prevalent among FSWs in Goroka and Kainantu in the EHP and are maintained by widespread high-risk sexual behaviors, including low use of condoms. Implications for their spread through the highway warrants increased efforts in intervention. Apart from a need to promote condom acceptance, distribution, and use, other high-risk sexual behavior and correlates identified in this study provide important considerations for intervention and control in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…None of the 200 sex workers tested in those two cities was HIV-positive, but once HIV enters such sexual networks, it is likely to spread rapidly. The rapid introduction of effective and appropriate prevention programmes could protect those sex workers and their clients from HIV (Gare et al, 2005).…”
Section: I D D L E E a S T A N D N O R T H A F R I C Amentioning
confidence: 99%
“…None of the 200 sex workers tested in those two cities was HIV-positive, but once HIV enters such sexual networks, it is likely to spread rapidly. The rapid introduction of effective and appropriate prevention programmes could protect those sex workers and their clients from HIV (Gare et al, 2005).…”
Section: I D D L E E a S T A N D N O R T H A F R I C Amentioning
confidence: 99%
“…18 Considering the importance of this population for the control of the HIV/AIDS epidemics, in a study carried out in New Guinea, the authors pointed out that the development of specifi c interventions for this population subgroup is a cost-effective strategy for the control of HIV dissemination. 19 This review shows that most of the studies that involved female SW used sampling techniques with non-probabilistic selection. When compared to the probabilistic samples, the convenience samples can generally be implemented more easily, faster and with fewer resources.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing mobility of persons makes this possibility more likely. Several studies have reported the presence of syphilis in some countries where yaws is endemic (e.g., Papua New Guinea) (306)(307)(308)(309)(310)(311), and it is unclear how the coexistence of venereal and nonvenereal transmission of treponemal infections might affect surveillance and assessment of eradication program success. This topic seems particularly relevant given the facts that patients in remote areas may not have access to sophisticated molecular techniques and that current serological tests are unable to discriminate among the agents of the human treponematoses.…”
Section: Cocirculation Of Syphilis and Yawsmentioning
confidence: 99%